The impact of background music on film audience’s attentional processes: Electroencephalography alpha-rhythm and event-related potential analyses - Kwon, Young-Sung; Lee, Jonghyun; Lee, Slgi (Sage) (Frontiers in Psychology, 2022)
Background music is an indispensable part of films and plays an important role in enhancing audiences’ attention to scenes. However, few studies have examined the cognitive effect of background music at the neurophysiological level. Using electroencephalography (EEG), the present study examines the effect of background music tempo on the viewer's attentional processes. Participants' (N = 24) EEG responses were recorded while the participants watched segments of action films in three conditions with variations on the presence and tempo of background music (i.e., no background music vs. slow-tempo music vs. fast-tempo music). These responses were analyzed using the alpha-rhythm suppression and event-related potential (ERP) P300, a brainwave indicator of attentional processes. The results suggest that participants' attention levels increased when background music was present (compared to when background music was absent), but there was no difference in participants’ attention levels based on tempo. The theoretical and practical implications of these findings are discussed.